Accelerating design of matching glass for phosphate fiber cores: Multi-parameter inversion model. (December 2020) - Yan, Sasa; Liu, Wenxiu; Han, Shuai; Du, Ying; Tao, Yiting; Chen, Yanping; Chen, Danping; Zhang, Liyan
Abstract: Based on twelve phosphate glasses compositions and properties, a composition-property model was established to predict the properties of matching glass for phosphate fiber cores, including thermal expansion coefficient (CTE), glass softening temperature (Ts ), glass transition temperature (Tg ), and refractive index (nd ). Under the composition constraints of this model, sensitivity analysis showed that the positive influence of these compositions on CTE, Ts, Tg and nd followed the order of Sb2 O3 > BaO > Na2 O > K2 O > P2 O5 > Nb2 O5 > La2 O3 > GeO2 > Al2 O3 > Y2 O3, Nb2 O5 > Y2 O3 > Al2 O3 > GeO2 > BaO > P2 O5 > La2 O3 > Na2 O > K2 O > Sb2 O 3, Nb2 O5 > Sb2 O3 > Al2 O3 > GeO2 > BaO > P2 O5 > La2 O3 > Na2 O > K2 O > Y2 O3, Sb2 O3 > Y2 O3 > Nb2 O5 > GeO2 = Al2 O3 > BaO > Na2 O > P2 O5 > K2 O > La2 O3 . Constraint-based probability distributions of properties were predicted via numerical simulation. This model can be extended to study multi-composition glasses, accelerating the glass design.